ANALISA HEADLOSS MAJOR DAN MINOR DI PT. PERTA DAYA GAS UNIT GAS PIPELINE SORONG - Nita Indriyani; Muthmainnah Ely (AGITASI: Jurnal Teknik Kimia, 2026)
PT. Perta Daya Gas is a joint venture subsidiary of PT. Pertamina Gas and PT. Indonesia Power. PT. Perta Daya Gas has 3 work units, namely PT. Perta Daya Gas Tambak Lorok - Semarang, PT. Perta Daya Gas Pesanggaran Unit 1 & 2 - Bali, and PT. Perta Daya Gas Gas Pipeline Sorong Unit which is tasked with providing natural gas transportation services from the MRS connection point of PT. Malamoi Olom Wobok to the 50 MW PLTMG MPP - Sorong with letter instructions No. 5195 / 09 / IP / 2019 dated December 30, 2019 regarding gas supply. This practical work aims to determine the gas transportation system used, the type of flow, and the effect of headloss on the pressure drop in the PT. pipeline. Perta Daya Gas Unit Gas Pipeline Sorong with the results of the natural gas transportation system used is an underground pipeline with a distance of 3.7 km and a turbulent flow type with an average Reynolds number of 19824.11, and major and minor headloss in October reached 20.72 m and 3.87 m, while the average headloss in the previous 3 months reached 14.17 m and 6.38 m caused by the pressure difference between upstream (PT. Malamoi Olom Wobok) and downstream (PT. Perta Daya Gas Unit Gas Pipeline Sorong) as well as the existence of predictive maintenance (PM) and corrective maintenance (CM), resulting in a pressure drop in October at each headloss reaching 1.99 bar and 0.49 bar.